Dosimeter arrangement for effective dose and isodose curves desterminations into craniofacial cavity - Campos Méndez, José Daniel (2023)
Tomographic dental imaging with cone beam computed tomography has developed so fast in Costa Rica, in the absence of investigations to determine the absorbed dose by the patients, we propose a TLD dosimeter array into RANDO Alderson phantom. Isodose curves were generated by ROOT Data Analysis Framework after an irradiation with Cs-137. The usefulness of the array to measure the dose into the phantom has been proved.